Pengaruh Role Model terhadap Pilihan Karir pada Mahasiswa Fakultas Kedokteran - Fatty Maulidira; Rizma Adlia Syakurah; Mariatul Fadilah; Hendarmin Aulia (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2015)
Introduction: Career as a doctor is not finished after graduate from basic medical education and clerkship. It will continue and there are many career options that can be choose, divided into clinician or non-clinician. There are many factors that influencing career choice, and one of them is role model. This research aimed to know how role model influence career choicing at students’ of Medical Faculty of Sriwijaya University. Method: This research is descriptive qualitative research. Data is acquired from Program Studi Pendidikan Dokter students by survey with open questions and in-depth interview.Results: 293 students become respondents of the survey and 8 students become key informants form in-depth interview. Based from informants, positive role model’ criterias are having a good-teaching method, looking good, having a good communication method, good attitude and behavior, skilled, and success in their career so that students want to follow those positive role model. Informants also said that negative role model’ criterias are having bad teaching method, bad looking and having bad attittude and behavior so that students don't want to follow role model’ trait. Conclusion: Positive role model can make students interested to follow positve role model’ career, and negative role model make students do not want to follow negative role model’ trait.